Access 2002 bible - Irwin, Michael R. (Hungry Minds, 2002)
Take charge of your data and run your business or organization both more efficiently and more successfully with the Access 2002 Bible, Gold Edition. Receive top-notch advice from Access experts, Cary N. Prague and Michael R. Irwin, which will help you to quickly master Access's premier database management capabilities and its hot new Web features. The Access 2002 Bible offers step-by-step instructions and practical examples and advice that equips you with everything you need to know to organize, present, analyze, and share data on a network or over the Web. Find comprehensive coverage of all new features and capabilities, including vastly improved Data Access Pages which gives users additional ways to provide information over the Web. Access 2002 carries several performance improvements and an enhanced new file format and every bit of that is addressed between the covers of the Access 2002 Bible, Gold Edition and the accompanying CD-ROM.